The Laterocavernous Sinus System: Venous Inflows, Venous Outflows, and Clinical Significance - Lv, Xianli; Jiang, Chuhan; Li, Youxiang; Liu, Lian; Liu, Jie; Wu, Zhongxue (World neurosurgery, 2011)
The laterocavernous sinus system is best defined as the entire territory served by the laterocavernous and the superior petrosal sinuses (SPS). The laterocavernous sinus is a small but important venous structure located between the two dural layers forming the lateral wall of the cavernous sinus and has been described as one of the principal drainage pathways of the deep and superficial middle cerebral veins. Several disease processes in the head involve the laterocavernous sinus. To evaluate and treat these diseases it is necessary for neuroradiologists not only to know selective angiography and embolization techniques, but also the territory of the laterocavernous sinus and venous watershed between the deep and superficial venous systems. In the present report the normal angiographic anatomy of the laterocavernous sinus system, its relationship with the deep and superficial venous systems, and its importance in clinical situations are outlined.